Apprentissage de l’offre active des services sociaux et de santé en français par module de simulation interprofessionnelle au bénéfice des francophones en situation minoritaire au Canada - Giroux, Isabelle; Savard, Jacinthe; Tyerman, Jane; Savard, Sébastien; Benoît, Josée; Kengneson, Cris-Carelle (Revista de Llengua i Dret, 2025)
Résumé La formation des futurs prestataires de soins à l’offre active (OA) des services sociaux et de santé (SSS) en français est essentielle pour permettre l’accès équitable à des services de qualité pour les francophones en situation minoritaire (FSM) au Canada. L’apprentissage par module de simulation interprofessionnelle est une avenue prometteuse à évaluer. L’objectif du présent travail est d’évaluer la satisfaction et l’efficacité perçue de l’apprentissage de l’OA des SSS en français à l’aide d’un module de simulation interprofessionnelle spécifique, le MODULE-IP-SIM-OA. En ce qui concerne la méthodologie, des stagiaires de programmes en SSS de l’Université d’Ottawa ont complété le dit module, suivi d’un débreffage synchrone et d’un questionnaire de rétroaction en ligne, entre mai et décembre 2023. Les 216 stagiaires issus de neuf disciplines ont rapporté des taux élevés de satisfaction et d’efficacité perçue concernant le MODULE-IP-SIM-OA et son débreffage. Cet apprentissage, jugé efficace par les stagiaires, pourrait avoir des retombées positives sur l’offre de services aux FSM afin d’atténuer les barrières linguistiques en santé. Resum La formació dels futurs professionals de la salut sobre l’oferta activa (OA) dels serveis socials i de salut (SSS) en francès és essencial per permetre un accés equitatiu a serveis de qualitat a les persones francòfones en situació minoritària (FSM) al Canadà. L’aprenentatge mitjançant un mòdul de simulació interprofessional és una via prometedora que cal explorar. L’objectiu d’aquest treball és avaluar el nivell de satisfacció i d’eficàcia percebuda de l’aprenentatge de l’OA dels SSS en francès amb l’ajuda d’un mòdul de simulació interprofessional específic, el MODULE-IP-SIM-OA. Pel que fa a la metodologia, diversos estudiants en pràctiques de programes de SSS de la Universitat d’Ottawa van completar aquest mòdul, seguit d’una sessió de debrífing síncrona i d’un qüestionari de valoració en línia, entre els mesos de maig i desembre de 2023. Els 216 estudiants, provinents de nou disciplines diferents, van aportar respostes que indiquen nivells alts de satisfacció i d’eficàcia percebuda en relació amb el MODULE-IP-SIM-OA i el debrífing posterior. Aquest aprenentatge, que els participants van considerar eficaç, podria tenir efectes positius en l’oferta de serveis als FSM per reduir les barreres lingüístiques en l’àmbit de la salut. Abstract Training future care providers in the active offer (AO) of social and health services (SHS) in French is essential for ensuring equitable access to quality services for Francophones in minority contexts (FMS) in Canada. Learning through an interprofessional simulation module is a promising approach that warrants evaluation. The purpose of this paper is to assess the satisfaction and perceived effectiveness of learning the AO of SHS in French using a specific interprofessional simulation module, the MODULE-IP-SIM-OA. Regarding methodology, between May and December 2023, trainees from SHS programs at the University of Ottawa completed this module, followed by a synchronous debriefing and an online feedback questionnaire. The 216 trainees from nine disciplines reported high levels of satisfaction and perceived effectiveness regarding the MODULE-IP-SIM-OA and its debriefing. This learning experience, considered effective by the trainees, could have positive impacts on service delivery to FMS and help reduce language barriers in healthcare. Resumen La formación de los futuros profesionales de la salud sobre la oferta activa (OA) de los servicios sociales y de salud (SSS) en francés es esencial para permitir un acceso equitativo a servicios de calidad a las personas francófonas en situación minoritaria (FSM) en Canadá. El aprendizaje mediante un módulo de simulación interprofesional es una vía prometedora que hay que explorar. El objetivo de este trabajo es evaluar el nivel de satisfacción y de eficacia percibida del aprendizaje de la OA de los SSS en francés con la ayuda de un módulo de simulación interprofesional específico, el MODULE-IP-SIM-OA. Con respecto a la metodología, varios estudiantes en prácticas de programas de SSS de la Universidad de Ottawa completaron este módulo, seguido de una sesión de debriefing síncrona y de un cuestionario de valoración en línea, entre los meses de mayo y diciembre de 2023. Los 216 estudiantes, provenientes de nueve disciplinas diferentes, aportaron respuestas que indican niveles altos de satisfacción y de eficacia percibida en relación con el MODULE-IP-SIM-OA y el debriefing posterior. Este aprendizaje, que los participantes consideraron eficaz, podría tener efectos positivos en la oferta de servicios a los FSM para reducir las barreras lingüísticas en el ámbito de la salud.

Reporting on knowledge, attitudes, and behaviours of pharmacists regarding the active offer of French language health services in Ontario: A quantitative survey study - Timony, Patrick; Leone, Arielle; Caron, Carolanne; Giguère, Pierre; Thabet, Pierre; Gauthier, Alain; Waite, Nancy M.; Landry, Christine (Canadian Pharmacists Journal / Revue des Pharmaciens du Canada, 2025)
Background: Patient–provider language discordances can negatively affect the availability, accessibility, acceptability, and quality (AAAQ) of pharmacy services as described by the AAAQ framework. With nearly 600,000 residents of Ontario identifying French as their mother tongue, the active offer (AO) of French language pharmacy services should be provided, yet little is known about pharmacists’ familiarity and use of AO. Methods: Ontario pharmacists completed an online survey measuring their knowledge, attitudes, and behaviours (KAB) regarding the AO for French language services (FLS). Demographics, including ability to converse in French, were collected. KAB AO scores were calculated and compared using descriptive and inferential statistics. Results: A total of 360 pharmacists completed the survey. The majority (65.1%) practiced in a primary care setting, 21.1% spoke French, and 71.8% lived in an area where less than 10% of the population were Francophone. Overall, AO scores were highest for attitude (3.8/5) and lowest for behaviours (2/5) and knowledge (1.8/5). Most pharmacists (62.8%) indicated an interest in AO training. Discussion: Gaps in KAB regarding AO for FLS by Ontario pharmacists resemble those observed throughout the health care system. Further training is suggested to address the lack of knowledge regarding AO, particularly its proactive nature, as well as strategies for its implementation. Conclusion: Although most participating pharmacists demonstrated gaps in AO knowledge and behaviour, many had favourable attitudes toward the importance of AO in the pharmacy setting and agreed that further training would be needed to improve their KAB. Further, the AO can address all 4 elements of the AAAQ framework.